Production of Food Grade Thickener from Benincasa Hispida - Noraziah, Abu Yazid; Theng, C. C (2013)

(untitled)
Benincasa Hispida is a fruit which has huge potential as the source of polysaccharides, which lead to its capability to become a good maintain material of thickener.